2020
DOI: 10.1177/1474515120919388
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle interventions after ablation for atrial fibrillation: a systematic review

Abstract: Background Risk factors of atrial fibrillation include diabetes, obesity and physical inactivity. Positive effects such as decreased atrial fibrillation burden have been reported for atrial fibrillation patients who have participated in lifestyle changing interventions after atrial fibrillation ablation treatment. Aim The aim of this study was to assess the evidence on the benefits and harms of lifestyle and risk factor management interventions in patients undergoing atrial fibrillation ablation. Method Our sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…A recent systematic review of four interventional studies (n=498 participants) found lifestyle and risk factor management significantly decreased AF episode severity, frequency, and duration (36). Supporting the notion of exercise as an AF-specific medical intervention, one previous study demonstrated improved sinus rhythm maintenance in patients with persistent AF, following external electrical cardioversion and rhythm control therapy (usual care) plus exercise, counselling, and dietary restriction compared to usual care alone (37).…”
Section: Secondary Prevention Of Afmentioning
confidence: 98%
“…A recent systematic review of four interventional studies (n=498 participants) found lifestyle and risk factor management significantly decreased AF episode severity, frequency, and duration (36). Supporting the notion of exercise as an AF-specific medical intervention, one previous study demonstrated improved sinus rhythm maintenance in patients with persistent AF, following external electrical cardioversion and rhythm control therapy (usual care) plus exercise, counselling, and dietary restriction compared to usual care alone (37).…”
Section: Secondary Prevention Of Afmentioning
confidence: 98%
“…A recently published review identified only 4 risk-factor intervention studies for patients treated with ablation for AF 32 . Tested interventions varied in elements, time, and setting and included physical exercise and psychoeducational consultations, nurse-led educational sessions, and dietician counseling sessions with personalized diet plans and moderate-intensity exercise training.…”
Section: Discussionmentioning
confidence: 99%
“…Otra rama importante de las funciones de la enfermera experta en FA es el manejo de los factores de riesgo modificables que pueden provocar o intensificar los episodios de FA 31 . Es importante identificar aquellos pacientes con obesidad o AOS para poder establecer un tratamiento adecuado para su control 32 .…”
Section: Discussionunclassified